2021
DOI: 10.1038/s41401-020-00584-2
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in key driver genes of pancreatic cancer: molecularly targeted therapies and other clinical implications

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal cancers, with a minimal difference between its incidence rate and mortality rate. Advances in oncology over the past several decades have dramatically improved the overall survival of patients with multiple cancers due to the implementation of new techniques in early diagnosis, therapeutic drugs, and personalized therapy. However, pancreatic cancers remain recalcitrant, with a 5-year relative survival rate of <9%. The lack of measures for early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 226 publications
0
50
0
Order By: Relevance
“…Pancreatic tumorigenesis results from the dysregulation of several core pathways and a myriad of genomic alterations [11]. Human pancreatic cancers have a specific mutational signature that include near-ubiquitous activating mutations of the oncogene KRAS (K Rat Sarcoma virus) and the frequent inactivation of the tumor suppressors TP53 (Tumor Protein P53), SMAD4/DPC4 (SMAD family Member4/Deleted in Pacreatic Carcinoma 4) e CDKN2A (Cyclin-Dependent KiNase inhibitor 2A) [12]. In general, KRAS mutations occur in stage 1 lesions (PanIN-1) and favor the initiation process; in PanIN-2, CDKN2A mutations emerge to induce further progression, while in stage 3 lesions (PanIN-3) and in invasive tumors, mutations of TP53 and SMAD4 drive the proliferation and expansion of cancer [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic tumorigenesis results from the dysregulation of several core pathways and a myriad of genomic alterations [11]. Human pancreatic cancers have a specific mutational signature that include near-ubiquitous activating mutations of the oncogene KRAS (K Rat Sarcoma virus) and the frequent inactivation of the tumor suppressors TP53 (Tumor Protein P53), SMAD4/DPC4 (SMAD family Member4/Deleted in Pacreatic Carcinoma 4) e CDKN2A (Cyclin-Dependent KiNase inhibitor 2A) [12]. In general, KRAS mutations occur in stage 1 lesions (PanIN-1) and favor the initiation process; in PanIN-2, CDKN2A mutations emerge to induce further progression, while in stage 3 lesions (PanIN-3) and in invasive tumors, mutations of TP53 and SMAD4 drive the proliferation and expansion of cancer [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Kras mutation is the most dominant oncogenic transformation in PDAC mutational profile confirmed in ∼90% of cases ( 2 ). The oncogenic Kras mutation leads to alteration of signaling pathways that are associated with the progression and metastasis of PDAC and is the main contributor of therapy recalcitrance ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…The schema represents the development of PDAC from pancreatic intraepithelial neoplasia (PanIN) 1, 2, and 3 in the precancer stages. Clinical sequencing results indicate the mutation frequencies of KRAS (99%), TP53 (85%), and SMAD4 (55%) and telomere shortening (91%), although numerous additional mutations occur during the metastatic process 59 60,61 but recent studies have shown that cancer metabolism alterations such as phosphatidylinositol‐3 kinase (PI3K), AKT, mammalian target of rapamycin (mTOR), and sirtuins are supposed to be involved at least from PanIN 2 stages and can elicit oxidative stress and damage responses associated with genomic instability 62,63 .…”
Section: Introductionmentioning
confidence: 99%
“…Clinical sequencing results indicate the mutation frequencies of KRAS (99%), TP53 (85%), and SMAD4 (55%) and telomere shortening (91%), although numerous additional mutations occur during the metastatic process. 59 Tissue abnormality has been associated with hypoxia and the Warburg effect at early and advanced stages of pancreatic carcinogenesis, 60 , 61 but recent studies have shown that cancer metabolism alterations such as phosphatidylinositol‐3 kinase (PI3K), AKT, mammalian target of rapamycin (mTOR), and sirtuins are supposed to be involved at least from PanIN 2 stages and can elicit oxidative stress and damage responses associated with genomic instability. 62 , 63 Such alterations may induce further mutations in advanced stages of PDAC.…”
Section: Introductionmentioning
confidence: 99%